Pain perception and thermographic analysis in patients with chronic lower back pain submitted to osteopathic treatment - Leal,Silvânia O (2019)
Introduction: Lower back pain (LBP), one of the main causes of pain, employee absenteeism and disabilities, exhibits a multifactorial and degenerative etiology, with different characteristics. Objective: a) analyze the acute effect of osteopathic treatment on the temperature of three dermatomes of patients with chronic lumbago; and b) assess the subjective pain perception of patients before and after an osteopathic session. Materials and methods: Quasi-experimental cross-sectional study of 14 individuals treated at a physical therapy clinic in Brasilia, Brazil. Data collection included physical therapy, pain scale (VAS), thermographic, and anthropometric assessment. Treatment consisted of a single osteopathic session. Results and conclusions: leg and foot temperature declined (∆% = 2.91 and 4.76%, respectively, p = 0005) in the innervations of 2 regions of interest (ROIs) of the L4 lower limb dermatome and pain levels decreased (∆% = 65.98 and 59.92%, p = 0.005) in the men and women, respectively. In addition, a strong correlation was observed between the maximum (r=0.742 and p-value = 0.002) and mean temperature variations of the lumbar region (r=0.733 and p-value = 0.003), according to the VAS. It was concluded that acute osteopathic treatment was efficient in varying the temperature at reference points of the dermatome analyzed and lowering pain perception, suggesting the effectiveness of the proposed treatment.